Earning management in Malaysian IPOs: The East Asian crisis, ownership control, and post-IPO performance - Ahmad Zaluki, Nurwati Ashikkin (Elsevier Science Ltd., 2011)
We find evidence of income-increasing earnings management in Malaysian IPOs, which occurs primarily for IPOs during a period of severe economic stress (the East Asian crisis). Within the high-ownership-concentration Malaysian market, post-IPO control concerns also appear to constrain IPO earnings management: owners seem willing to accept reduced IPO proceeds and signaling opportunities to increase the likelihood of retaining control of the company post-IPO. The requirement to provide a profit guarantee does not seem to greatly affect earnings management.IPO companies engaging in aggressive income-increasing earnings management have significantly worse market-based performance than their more conservative counterparts, but again only for IPOs issued during the economic crisis period. Overall, the results suggest that personal liquidity concerns are an important factor in IPO decisions during the economic crisis.